Governing the Nexus Water, Soil and Waste Resources Considering Global Change - Kurian, Mathew.; Kurian, Mathew.; Ardakanian, Reza.; Ardakanian, Reza. (Springer International Publishing : Imprint: Springer, 2015)
Based on papers and discussions surrounding the international kick-off workshop of the UNU-FLORES institute, held in Dresden, Germany in November, 2013, this book elaborates on key themes of the nexus approach to management of environmental resources- water, soil and waste. The first three chapters address issues of global change and the nexus approach to environmental governance. Discussion includes concepts of poverty-environment nexus, adapative management, questions surrounding inter-sectionality, interactionality and hybridity. Chapters 4, 5 and 6 elaborate on the challenges of financing infrastructure projects, including questions of accountability and autonomy, in the context of decentralization and deregulation. Issues relating to the role of central transfers, taxes and tariffs and potential applications of results-based financing approaches to support sustainable service are also discussed. Chapters 7, 8 and 9 explore strategies for implementation, focusing on European experience with application of life-cycle cost analysis in water and wastewater projects, the use of an agro-ecology framework to support wastewater reuse in agriculture and applications of data visualization techniques for evidence based decision making. The book concludes with a chapter by the editors, whose title expresses perhaps the most difficult question faced by development planners in addressing challenges of global change: Policy is Policy and Science is Science: Shall the Twain Ever Meet?